设A,B为随机事件,A与B都不发生,用事件运算表示为( )
A: [img=41x18]18030f3b8ed7565.jpg[/img]
B: [img=42x21]18030f3b9a13db9.jpg[/img]
C: [img=63x21]18030f3ba472fa4.jpg[/img]
D: [img=32x24]18030f3baf6ce9a.jpg[/img]
A: [img=41x18]18030f3b8ed7565.jpg[/img]
B: [img=42x21]18030f3b9a13db9.jpg[/img]
C: [img=63x21]18030f3ba472fa4.jpg[/img]
D: [img=32x24]18030f3baf6ce9a.jpg[/img]
举一反三
- 设A,B为随机事件,A发生而B不发生,用事件运算表示为() A: [img=41x18]18030f3b866c33e.jpg[/img] B: [img=28x18]18030f3b93727e6.jpg[/img] C: [img=63x21]18030f3b9dc167c.jpg[/img] D: [img=32x24]18030f3ba8c7eba.jpg[/img]
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803da40b5dbfd6.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803da40ac7a8ce.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803381b293bffb.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]17de66bf652c147.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32